Is Intra-Articular Injection of Synvisc Associated with a Delay to Knee Arthroplasty in Patients with Knee Osteoarthritis?. (October 2019) - Ong, Kevin L.; Runa, Maria; Lau, Edmund; Altman, Roy
Objective: There is debate about the effectiveness of intra-articular (IA) hyaluronic acid (HA) injections. We asked the following questions: (1) What is the epidemiology of IA HA use in knee arthroplasty (KA) patients? (2) Is Synvisc associated with a delay to KA? (3) Is there a difference in the delay to KA with the number of HA courses? Design: The Optum Clinformatics data set (2006–June 2016) was used to identify patients with knee osteoarthritis (OA). Patients who did not receive IA HA were identified, along with those who received Synvisc or non-Synvisc HA. The median duration from knee OA to KA was compared using quantile regression modeling with propensity score weighting. The trend in time to KA with each HA course was evaluated. Results: Of 4, 027, 848 knee OA patients, 141, 305 patients underwent KA. Overall median time from knee OA diagnosis to KA was 1.2 years (average: 1.9 ± 1.9 years; interquartile range of 0.4-2.8 years). HA patients had significantly longer adjusted median time to KA by at least 7 months ( P < 0.001). After adjusting for the time to HA and number of injections, Synvisc patients had 1.7 months longer time to KA than non-Synvisc HA patients ( P < 0.001). There was a trend toward longer time to KA with more HA courses. Conclusions: Most KA patients did not use HA (73.7%) and when received, it was associated with a longer median time to KA by at least 7 months, though the cause and effect could not be examined. The delay to KA increased with more HA courses.